2016
DOI: 10.1093/ejcts/ezw290
|View full text |Cite
|
Sign up to set email alerts
|

Reoperations and catheter interventions in patients with transposition of the great arteries after the arterial switch operation

Abstract: The frequency of reoperations and percutaneous interventions in patients with TGA after the ASO remains low. The majority of the procedures are performed because of pulmonary stenosis and recoarctation of aorta. Cardiac anomalies associated with TGA have a significant impact on the incidence of reoperation and reintervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 17 publications
0
35
1
Order By: Relevance
“…3 Previous single center studies have reported incidences of pulmonary artery stenosis requiring intervention ranging from 3.8% to 28%. [4][5][6] Pulmonary artery angioplasty and/or stenting have been the most common procedures performed in these patients. [4][5][6][7][8][9] We encountered aorto-pulmonary (AP) fistulae and coronary artery compression during pulmonary artery stent procedures in this population.…”
Section: Introductionmentioning
confidence: 99%
“…3 Previous single center studies have reported incidences of pulmonary artery stenosis requiring intervention ranging from 3.8% to 28%. [4][5][6] Pulmonary artery angioplasty and/or stenting have been the most common procedures performed in these patients. [4][5][6][7][8][9] We encountered aorto-pulmonary (AP) fistulae and coronary artery compression during pulmonary artery stent procedures in this population.…”
Section: Introductionmentioning
confidence: 99%
“…In this report, 309 patients were included with all echocardiographic measurements that were performed in standardized fashion (n=1844). The rate of reintervention was 5%, which is at the lowest part of the published ranges 5,[8][9][10][11] . There was no difference in the pressure gradient in the presence or absence of an associated ventricular septal defect.…”
Section: Regarding Limited Buttons Resection Technique a Data Of 120mentioning
confidence: 86%
“…The reported incidence of reoperation related to pulmonary stenosis after the arterial switch operation ranges from 5-30% 5,[8][9][10] . Because the pulmonary artery pressure gradient can vary with the somatic growth, we sought to examine the behavior of the pulmonary artery pressure gradient over time and to determine the contributing factors and its relationship with the need for reintervention.…”
Section: Introductionmentioning
confidence: 99%
“…Most reoperations after the ASO occur after the first postoperative year. Freedom from reoperation has been reported in a range of 79% to 97% at 10 years [12,[14][15][16][17][18], 76% to 87% at 15 years [14,15,18,19], and 86% at 25 years (Table 1) [12].…”
Section: Current Outcomes Of the Asomentioning
confidence: 99%